Spontaneous HIV controllers exhibit preserved immune parameters in peripheral blood and gastrointestinal mucosa (2015)
ABSTRACT: Background: HIV infection induces several gradual alterations on the peripheral and mucosal immune systems, with different magnitudes between infected individuals. In this regard, spontaneous HIV controllers exhibit either low or undetectable viral loads in the absence of treatment along with decreased immune alterations compared to HIV progressors. Yet, it is unknown how similar immune peripheral and mucosal parameters are when comparing HIV controllers to uninfected individuals. Methods: We evaluated a cohort of 11 HIV controllers who were compared to 20 seronegative donors. Peripheral blood (PB) and gut associated lymphoid tissue (GALT) samples were obtained to analyze the following: 1) the frequency and phenotype of immune cells by flow cytometry; 2) the expression of apoptotic molecules by immunohistochemistry; 3) the expression of transcriptional factors associated with T cell profiles by real time PCR; and 4) the serum level of microbial translocation by an enzymatic reaction. Results: We found that HIV controllers have a conserved frequency of most immune cell populations in PB andGALT, but a reduced percentage of CD4 T cells. The immune activation levels were similar in both groups of individuals, as well as the expression of cleaved caspase-3, transcriptional factors, and the level of microbial translocation. Interestingly, the frequency of CD8 T cells expressing HLA-DR but not CD38, previously associated with high effector functions, were preserved in HIV controllers. Conclusions: Our results suggest that despite the infection, HIV controllers have preserved immune parameters, which can be associated with the spontaneous control of viral replication.